1989
DOI: 10.1007/bf00027780
|View full text |Cite
|
Sign up to set email alerts
|

Performances of three bacterial assays in toxicity assessment

Abstract: Three differing bacterial toxicity assays were compared: the 'Microtox' test, (Photobacterium phosphoreum luminescence inhibition assay), the 'oxygen consumption of activated sludge' assay (ISO 8192), and the 'Glucose U-14 C mineralization' assay (the rate of release of 4 CO2 by 'Escherichia col£). Metals, amines, halogenated alcans, chlorophenols, aromatic hydrocarbons, surfactants, and pesticides were screened for their toxic activity.Results showed satisfactory repeatability of the three bacterial assays wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Microorganisms are useful in ecotoxicity testing because they may be evaluated over a short time and they occupy trophic levels in which bioaccumulation and/or bioconcentration are potential problems [ 74 ]. Bacterial toxicity tests measure a wide variety of endpoints including mutagenicity tests [ 75 ], population growth [ 76 ], CO 2 production [ 77 ], enzyme biosynthesis [ 78 ], glucose mineralization [ 79 ], and bioluminescence inhibition [ 80 ].…”
Section: Toxicity Of (Bio)surfactants and Dispersants On Organismsmentioning
confidence: 99%
“…Microorganisms are useful in ecotoxicity testing because they may be evaluated over a short time and they occupy trophic levels in which bioaccumulation and/or bioconcentration are potential problems [ 74 ]. Bacterial toxicity tests measure a wide variety of endpoints including mutagenicity tests [ 75 ], population growth [ 76 ], CO 2 production [ 77 ], enzyme biosynthesis [ 78 ], glucose mineralization [ 79 ], and bioluminescence inhibition [ 80 ].…”
Section: Toxicity Of (Bio)surfactants and Dispersants On Organismsmentioning
confidence: 99%
“…However, we did not culture microorganisms to establish relationships between identity and copper resistance, nor determined their histamine production potential. Considering (i) the relative low copper exposure concentrations applied in this study compared to the observed potentials to resist copper; (ii) the fact that the copper concentration in meat is only slightly enhanced after copper exposure; and (iii) that the bioavailable copper concentration in the digestive tract – the major habit for microorganisms – was not determined, it is difficult to evaluate the importance of resistance of bacteria to copper in relation to the observed community changes in water and meat. The effect of copper may also simply relates to the fitness of bacteria (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of copper on microbial community structure in water may depend on several factors: among others, the exposure concentration, the chemical form of the toxic substance and species‐specific attributes to deal with copper . Many species of bacteria show resistance to copper: among others, Pseudomonas syringae, Xanthomonas campestris pv.…”
Section: Discussionmentioning
confidence: 99%
“…The effective concentration of chemical or test sample causing a 50% inhibition of light (EC50) after a specified period of time (e.g., 15 min) is reported [3]. Use of the Microtox bioassay has been extensive and has included evaluation of many chemicals in aqueous solution [4–8], contaminated groundwaters and wastewaters [9–12], and aqueous and organic extracts of contaminated soils and sediments [13–16].…”
Section: Introductionmentioning
confidence: 99%